2006
DOI: 10.1002/bip.20534
|View full text |Cite
|
Sign up to set email alerts
|

Handedness control of peptide helices by amino acid side‐chain chirality: Ile/aIle peptides

Abstract: A set of four hexapeptide sequences, each characterized by four strongly helicogenic Aib residues and all combinations of two isomeric Ile/aIle residues at positions 2 and 5, was synthesized by solution methods and fully characterized. A detailed solution (by FT-IR absorption, NMR, and CD techniques) and solid/crystalline state (by X-ray diffraction) conformational investigation allowed us to validate our assumption that all four peptides are folded in well-developed 3(10)-helical structures. However, the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 67 publications
1
12
0
Order By: Relevance
“…Pellet techniques have been used in many laboratories, for a variety of samples including biomolecules, [32][33][34][35][36][37][38][39][40][41][42][43] both in the UV-vis (ECD) and in the IR (VCD).…”
Section: Pelletsmentioning
confidence: 99%
“…Pellet techniques have been used in many laboratories, for a variety of samples including biomolecules, [32][33][34][35][36][37][38][39][40][41][42][43] both in the UV-vis (ECD) and in the IR (VCD).…”
Section: Pelletsmentioning
confidence: 99%
“…A few years ago, we made efforts to address the issue of handedness control of peptide helices via amino acid side‐chain chirality by investigating the conformational properties of terminally protected (or blocked), helical diastereomeric hexapeptides rich in Ile or a Ile (where a stands for allo ) residues (Figure ) .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, four stereoisomers are possible. These isomers are: l ‐Ile [(2 S ,3 S )‐2‐amino‐3‐methyl‐valeric acid], l ‐ allo ‐Ile [(2 S ,3 R )‐2‐amino‐3‐methyl‐valeric acid], d ‐Ile [(2 R ,3 R )‐2‐amino‐3‐methyl‐valeric acid] and d ‐ allo ‐Ile [(2 R ,3 S )‐2‐amino‐3‐methyl‐valeric acid] (Andreetto et al ., ). The structures of the four Fmoc‐protected Ile configurational isomers used in this study are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…With the exception of glycine, the remaining 19 proteinogenic amino acids contain at least one chiral carbon atom, with isoleucine (Ile) and threonine also containing a second chiral carbon atom. Such chiral centers allow the existence of amino acid enantiomers (Andreetto et al, 2006;Ilisz et al, 2010). It is well known that L-and D-enantiomeric forms of amino acids substituted into peptides and proteins can have profoundly different effects on stability and biological activity (Chen et al, 2005;Kondejewski et al, 1999;Lee et al, 2004;Oren and Shai, 1997;Papo and Shai, 2005).…”
Section: Introductionmentioning
confidence: 99%